In‐Plane Mechanically Gradated 2D Materials: Exploring Graphene/SiC/Silicene Transition via Full Atomistic Simulation. Issue 1 (29th October 2018) - Zhang, Hanming; Cranford, Steven W.
Abstract: The emergence of 2D materials has resulted in many platforms with promising applications. One possibility is to combine two (or more) systems in a multilayered structure. However, can such materials transition in‐plane? Here, the potential of graded transition from graphene to silicene, via 2D silicon carbide is explored. The work focuses on mechanical performance of a two‐phase gradated system under uniaxial stress. The percentage of the carbon/silicon in‐plane, to explore the resulting effects on strength and stiffness using full atomistic molecular dynamics (MD) is varied. Carbon atom placement of 0% to 100% in nine increments with random substitution, is tested using both single‐bond and mixed‐bond homogeneous and two‐phase gradated models. Stiffness and strength can be predicted by a simple model accounting for proportional bond distributions. It is demonstrated that the inclusion of nominal amounts of Si–C bonding results in drastic changes in mechanical response when compared to graphene, tolerant to change across a wide range of distributions, suggesting a "weakest link" effect. For the two‐phase gradated systems, stress contour plots correlate with changes in silicon‐to‐carbon ratios. The work demonstrates the feasibility of a new class of 2D in‐plane gradated materials with tunable stiffness, predictable strength, and controlled failure. Abstract : Full atomistic molecular dynamics is implemented to evaluate the mechanical response of systems with various randomly distributed carbon and silicon contents, from 100% carbon (graphene) to 100% silicon (silicene). Ultimate failure strength and elastic stiffness is characterized theoretically by the Si:C ratio to assess the potential of in‐plane gradated systems with spatially varying atomistic distributions.